PENGARUH PENDIDIKAN KEWIRAUSAHAAN TERHADAP AKTIVITAS WIRAUSAHA MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Nuraisah '; Gimin '; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: The objectives of this research were to know the effect of entrepreneurship education student of economic education FKIP Riau University. The population of this research was the student of economic education FKIP Riau University force as 2013, 2014, and 2015 amount 253 people and the sample amount 37 people. The collected data used questionnaire and interviews. Data analysis of this research used simple linier regression. Research result based on simple linier regression showed that entrepreneursihip education influence on entrepreneurship activity student of economic education student force as 2013, 2014, and 2015 in FKIP Riau University, this can be seen from a constant value (a) of 19,452 and the value coefisien regression (b) of 1,077 with a regresiion equation 19,452 + 1,077. According the calculation of R (R squer change) obtained a value of 0,159. It means that the contribution of entrepreneurship education on entrepreneurship activity by 15,9%. Based on the results of research, suggestions or recommendations from researchers is that students should be able to maintain their entrepreneurial skills as a supporting factor in maintaining the entrepreneurial activities they have in order to facilitate the achievement of the goals they want to achieve and encourage business success in the future.Key Word :Entrepreneurship Education, Entrepreneurship Activity